(untitled) (Lead City International Journal of Library, Information & Communication Sciences, 2025)
Service delivery by Health Information Management (HIM) practitioners contributes to patients’ healthcare services. Previous studies reported that the services received by patients are declining. This decline has given rise to reluctance in seeking medical attention, adhering to medical guidance, and participating in health initiatives. Studies have shown that personal factors in university teaching hospitals can affect service delivery. However, the variable has not been fully measured in the literature to determine its influence on service delivery. Therefore, this study investigated the influence of personal factors on service delivery. HIM practitioners in university teaching hospitals, South-West, Nigeria. The study employed survey research design. The population comprised 417 HIM practitioners and 468,654 outpatients. Total enumeration was used for HIM practitioners and Krejcie and Morgan’s formula was used to derive the sample size of 422 outpatients. Cronbach’s alpha reliability coefficients for the constructs ranged from 0.70 to 0.97. The response rate was 100% and 92% for outpatients and HIM practitioners respectively. Data were analysed using descriptive and inferential (simple and multiple regression) statistics. Findings revealed personal factors have a positive and significant influence on service delivery (Adj.R2 = 0.17, F(1, 383) = 77.38, p < 0.05). The study concluded that personal factors enhanced service delivery of health information management practitioners in university teaching hospitals in South-West, Nigeria.